Analyzing credit risk transmission to the non-financial sector in Europe: a network approach - Christian Gross; Pierre Siklos (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
Using variance decompositions in vector auto-regressions (VARs) we model a high-dimensional network of European CDS spreads to assess the transmission of credit risk to the non-financial corporate sector. Our findings suggest a sectoral clustering in the CDS network, where financial institutions are located in the center and non-financial as well as sovereign CDS are grouped around the financial center. The network has a geographical component reflected in differences in the magnitude and direction of real-sector risk transmission across European countries. While risk transmission to the non-financial sector increases during crisis events, risk transmission within the non-financial sector remains largely unchanged.
Keywords: C01; C32; G01; G15; 330; networks; financial-real linkages; connectedness; systemic risk; credit risk; contagion